"Quick, that auction ends soon!" finding low-cost teaching materials for special collections librarians. Issue 3 (2nd October 2021) - Germek, George P.
ABSTRACT: Despite curtailed budgets, academic libraries can create new or augmented instructional platforms and expand their institutional offerings with low-cost collections acquisitions obtained from commercial internet auction sites, flea markets, and retail sites. Using these low cost acquisitions, librarians can create numerous interactive, primary research exercises that result in enhanced special collections use and improved student engagement.